As representações sociais das mudanças do clima e suas implicações no processo de territorialização: os Bijagós da ilha de Formosa, Guiné-Bissau - Santy, Boaventura Rodrigues Vaz Horta (2012)
The study describes and analyzes sociologically, from a qualitative approach, the social representations of the people of the island of Formosa Bijagó about possible threats related to climate change, its consequences in terms of the form of territorial occupation and way of life characteristic of that group. For this, we adopted the following methodological procedures: a) A review of the state of the art about the concepts of vulnerability related to climate change, the increasing vulnerability, risk and social representations, b) documentary research and fieldwork. For Bijagó the natural and the social are inextricably linked, to the extent that a crisis in the social system would have negative effects on natural sistem. Thus, the adverse changes that are occurring in nature around them, would be signs of displeasure from their ancestors about the differences and crises with the community, which are in power to control and manipulate the events of nature.